A Sociopolitical Analysis of John Arden’s Serjeant Musgrave’s Dance: Futility of Being a Wacky Mutineer - Hammad Abed, Hamid; Ubeid, Ahmed .H (Al-Adab Journal, 2020)
Futility of being a wacky mutineer is one of the significant matters used in Arden’s Serjeant Musgrave’s Dance. This mainly implied matter exploited by Arden to intentionally criticize the war-makers and at the same time to expose the mutineer’s attempt in making change via infuriating the townsfolk to revolt against the inequitable authority. This study aims at visualizing the real confrontation and struggle between Musgrave and the representatives of the dominating regime. It is divided into two sections and a conclusion. Section one deals with John Arden, the playwright, who is constantly a political radical, cautious of authority and exceeding social institutions. In section two, the sociopolitical analysis of Serjeant Musgrave’s Dance is dedicated to explain how Arden is often viewed as one of so prominent playwrights who has created a theatrical rebellion in English drama.